2014
DOI: 10.1007/s10900-014-9949-0
|View full text |Cite
|
Sign up to set email alerts
|

Latino Parents’ Perceptions of the HPV Vaccine for Sons and Daughters

Abstract: Latinas have the highest incidence of cervical cancer. Latino parents' perceptions of the human papillomavirus (HPV) and willingness to have their sons and daughters vaccinated in Utah is largely unknown. Latino parents/guardians of children ages 11-17 years were recruited from two community organizations (N = 52) to participate in a mini-survey and focus group. Guided by the social ecological framework, a Latina facilitator conducted five focus groups that were recorded, transcribed and translated. Descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 12 publications
9
69
0
1
Order By: Relevance
“…Rather, qualitative research suggests that parents found open-ended communication ambiguous, frustrating and worrying, leading them to delay HPV vaccination for their adolescents. 61,71,77,78,98,99 Instead of encouraging shared decision making, mixed messages appeared to lead to a "default" communication style in which neither providers nor parents engaged in the decision-making process. 110 Findings also provide evidence of communication disparities in terms of who receives a provider recommendation for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rather, qualitative research suggests that parents found open-ended communication ambiguous, frustrating and worrying, leading them to delay HPV vaccination for their adolescents. 61,71,77,78,98,99 Instead of encouraging shared decision making, mixed messages appeared to lead to a "default" communication style in which neither providers nor parents engaged in the decision-making process. 110 Findings also provide evidence of communication disparities in terms of who receives a provider recommendation for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…84 In contrast, qualitative studies with parents from racial/ethnic minority backgrounds suggested some degree of dissatisfaction with HPV vaccine communication, with some parents reporting too little information, limited opportunities to ask questions, or ambiguous recommendations. 61,71,77,78,98,99 For these parents, the perception that providers were withholding information was a source of confusion that introduced doubt about the value of HPV vaccination, discouraged vaccine acceptance, and in some cases undercut parents' trust in providers. 61,71,77,78,98,99 Parents emphasized their desire for clear, unambiguous messages from providers about the importance of HPV vaccination.…”
Section: Satisfactionmentioning
confidence: 99%
See 3 more Smart Citations